(untitled) (LEGAL DIALOGICA, 2025)
This research aims to find out and analyze the arrangements regarding the duties and functions of Satpol PP Law No.. 23 of 2014. As well as to find out and analyze whether the actions of the Satpol PP in the action of the Mattoanging Care Alliance are in accordance with the limits of the authority given. This study uses a normative juridical law research method by focusing on analyzing primary data and secondary data using qualitative data analysis techniques The results of this study show that (1). The Regulation on the Duties and Functions of Satpol PP in Law No. 23 of 2014 stipulates that Satpol PP is tasked with enforcing Regional Regulations and Regional Head Regulations, organizing public order and tranquility, and providing protection to the community. (2).The act of physical violence committed by the Civil Service Police Unit (Satpol PP) in handling the demonstration of the Mattoanging Care Alliance is not in accordance with the limits of authority given by laws and regulations. Based on Article 255 paragraph 1 of Law Number 23 of 2014 concerning Regional Government, Satpol PP is tasked with enforcing Regional Regulations and Regional Head Regulations, organizing public order and public order, and providing protection to the community. The three main tasks are administrative and do not include repressive measures or the use of force. Research Recommendations It is suggested that the capacity of Satpol PP human resources be increased through continuous training based on legal principles and human rights. In addition, strengthening the supervision and accountability mechanism is needed to ensure that the actions of the Satpol PP are not repressive and still uphold the ethics of public service and democracy. In addition, a transparent evaluation and accountability mechanism is needed to prevent future abuse of authority. Abstrak Penelitian ini bertujuanUntuk mengetahui dan menganalisis pengaturan mengenai tugas dan fungsi Satpol PP Undang – Undang No..23 Tahun 2014. Serta untuk mengetahui dan menganalisis apakah tindakan satpol pp dalam aksi aliansi peduli Mattoanging sudah sesuai dengan batas-batas kewenangan yang diberikan. Penelitian ini menggunakan metode penelitian hukum yuridis Normatif dengan berfokus menganalisis bahan hukum primer dan bahan hukum sekunder menggunakan teknis analisis data kualitatif Hasil Penelitian Ini menunjukkan Bahwa (1).Pengaturan Mengenai Tugas Dan Fungsi Satpol PP Dalam Undang – Undang No. 23 Tahun 2014 mengatur bahwa Satpol PP bertugas menegakkan Peraturan Daerah dan Peraturan Kepala Daerah, menyelenggarakan ketertiban umum dan ketenteraman, serta memberikan perlindungan kepada masyarakat. (2).Tindakan kekerasan fisik yang dilakukan oleh oknum Satuan Polisi Pamong Praja (Satpol PP) dalam penanganan aksi demonstrasi Aliansi Peduli Mattoanging tidak sesuai dengan batas-batas kewenangan yang diberikan oleh peraturan perundang-undangan. Berdasarkan Pasal 255 ayat 1 Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah, Satpol PP bertugas menegakkan Peraturan Daerah dan Peraturan Kepala Daerah, menyelenggarakan ketertiban umum dan ketenteraman masyarakat, serta memberikan perlindungan kepada masyarakat. Ketiga tugas pokok tersebut bersifat administratif dan tidak mencakup tindakan represif atau penggunaan kekerasan. Rekomendasi Penelitian Ini disarankan agar dilakukan peningkatan kapasitas sumber daya manusia Satpol PP melalui pelatihan berkelanjutan yang berbasis pada prinsip-prinsip hukum dan hak asasi manusia. Selain itu, penguatan mekanisme pengawasan dan akuntabilitas diperlukan guna memastikan bahwa tindakan Satpol PP tidak bersifat represif serta tetap menjunjung tinggi etika pelayanan publik dan demokrasi.Selain itu, diperlukan mekanisme evaluasi dan akuntabilitas yang transparan untuk mencegah terjadinya penyalahgunaan wewenang di masa mendatang.